2022
DOI: 10.1021/acs.joc.2c01885
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Generations of Secondary and Tertiary Silyl Radicals from Silylboranes Using an Alkoxide Cocatalyst

Abstract: Silyl radicals are valuable species to prepare diverse organosilicon compounds. However, unlike stable tertiary silyl radicals, the use of secondary silyl radicals has been problematic in silylation reactions due to their instability. Here, we present photocatalytic in situ generations of both secondary and tertiary silyl radicals by one-electron oxidation of ate complexes, formed from silylboranes and an alkoxide cocatalyst, achieving highly efficient hydrosilylation and deuterosilylation of electron-rich alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Based on our investigation and previous findings, , we propose a plausible mechanism for this visible-light-induced alkene silyl-oximation as depicted in Scheme . First, photoinduced N–NO bond homolysis of N -nitrosamines produces an aminyl radical and a persistent NO radical.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Based on our investigation and previous findings, , we propose a plausible mechanism for this visible-light-induced alkene silyl-oximation as depicted in Scheme . First, photoinduced N–NO bond homolysis of N -nitrosamines produces an aminyl radical and a persistent NO radical.…”
supporting
confidence: 66%
“…Among them, an efficient method is catalytically transferring silyl from silylboronic pinacol esters (SPEs) to form C–Si bonds (Scheme b). , However, most traditional methods to construct C–Si bonds from silylboranes involve the use of noble and toxic transition-metal catalysts . To overcome these major drawbacks, researchers have increasingly focused on the Lewis base activation strategy, which is based on the weak Lewis acidity of SPEs, to decrease the redox potential of SPEs and generate silyl radicals in the presence of photoredox catalysts, this strategy was elegantly explored by Tanaka, Zhang, Shibata, and Ohmiya, among others . Although significant progress has been made, expensive photocatalysts and massive amounts of strong Lewis bases are needed for these reactions.…”
mentioning
confidence: 99%
“…Notably, Shibata’s group pioneered the research on t BuOK-mediated C–Si, C–C, and C–N bond formation via C–F bond cleavage, in which silyl radicals were generated under excess base conditions (Scheme a) . Through literature research, silyl radicals were normally employed in Giese-type reactions (Scheme b); − ,,, it is unclear whether the endocyclic ring scission of heteroarene is feasible via silyl radical addition and subsequent β-elimination to achieve dearomatization (Scheme c). If successful, we believe that such a tactic would not only provide a new prospective and complementary pathway for functionalization by endocyclic carbon–heteroatom bond scission in heteroaromatic systems, but also give a fascinating insight into silyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Ito et al demonstrated in a ground-breaking study that UV radiation causes silylaminoboronate to undergo homolysis, resulting in the formation of silyl radicals . The generation of silyl radicals via photoredox catalysis from silylboronate was reported by Poisson, Ohmiya, and Tanaka, respectively (Scheme a) . Notably, Shibata’s group pioneered the research on t BuOK-mediated C–Si, C–C, and C–N bond formation via C–F bond cleavage, in which silyl radicals were generated under excess base conditions (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%